CLASSIFICATION OF MAIZE LINES ACCORDING TO THE CONTENT OF ALLELES OF ‘C’ TYPE FERTILITY-RESTORER GENES - G. Ya. Krivosheev (Зерновое хозяйство России)
Self-pollinated lines of maize have been identified according to the content of alleles of fertility-restorer genes Rf4, Rf5, Rf6 of ‘C’ type of CMS. Genotype of the line SP 286 – rf4 rf4 rf5 rf5 rf6 rf6 possesses restorer genes in recessive state. Genotype of the line SP 357 possesses restorer genes in dominant state (Rf4, Rf5, Rf6). Genotype of the lines SP 275 and SP 331 possesses two restorer genes in dominant state and one gene in recessive state. The study results allow forecasting reaction of the lines on sterile cytoplasm ‘C’ type of CMS. Self-pollinated line SP 286 is going to possess sterile progeny in hybridization with any sterile lines. Fertility will completely be restored in any hybridization with the line SP 357. Fertility restoration in any hybridization with the lines SP 257 and SP 331 will depend on the genotype of the chosen pair. Classification of lines according to the content of fertility-restorer genes will allow finding a suitable program of transferring maize hybrids on a sterile basis and determining position of lines in a hybrid.